Characterization of gut microbiota signatures in Indian preterm infants with necrotizing enterocolitis: a shotgun metagenomic approach - Devarajalu, Prabavathi; Attri, Savita Verma; Kumar, Jogender; Dutta, Sourabh; Kabeerdoss, Jayakanthan (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionNecrotizing enterocolitis (NEC) is an inflammatory bowel disease that primarily affects preterm infants. Predisposing risk factors for NEC include prematurity, formula feeding, anemia, and sepsis. To date, no studies have investigated the gut microbiota of preterm infants with NEC in India.MethodIn the current study, shotgun metagenomic sequencing was performed on fecal samples from premature infants with NEC and healthy preterm infants (n = 24). Sequencing was conducted using the NovaSeq X Plus platform, generating 2 × 150 bp paired-end reads. The infants were matched based on gestational age and postnatal age.ResultThe median time to NEC diagnosis was 9 days (range: 1–30 days). Taxonomic analysis revealed a high prevalence of Enterobacteriaceae at the family level, with the genera Klebsiella and Escherichia particularly prominent in neonates with NEC. No statistically significant differences in alpha or beta diversity were observed between stool samples from infants with and without NEC. Linear regression analysis demonstrated that Enterobacteriaceae were significantly more abundant in stool samples from infants with NEC than without NEC (q < 0.05). Differential abundance analysis using Linear Discriminant Analysis Effect Size (LEfSe) identified Klebsiella pneumoniae and Escherichia coli as enriched in the gut microbiota of preterm infants with NEC. Functional analysis revealed an increase in genes associated with lipopolysaccharide (LPS) O-antigen, the type IV secretion system (T4SS), the L-rhamnose pathway, quorum sensing, and iron transporters, including ABC transporters, in stool samples from infants with NEC.ConclusionThe high prevalence of Enterobacteriaceae and enrichment of LPS O-antigen and T4SS genes may be associated with NEC in Indian preterm infants.